An Analysis of the Day-of-the-Week Effect in the Indian Stock Market: Evidence from Bombay Stock Exchange - Malavalli, Nagesh; Sathyanarayana, S (Ushus Journal of Business Management, 2015)
A major apprehension in the market efficiency hypothesis is the existence of calendar anomalies or seasonality in the stock market returns. One of the most prominent calendar anomalies is the”Day-of-the-Week” effect. Thus, investors are more worried about which day of the week is the best day for the trade. The current study aims to study empirically the Day-of-the-Week effect anomaly in the emerging stock market of a developing economy like India for the period 2004 to 2014 using end of day data for the benchmark Indian equity market index BSE Sensex using dummy variables regression. Empirical results conclude that BSE Sensex does not show any presence of “Day-of-the-Week” effect or seasonality. Hence one can conclude that the BSE Index is efficient and there is no Day-of-the-Week anomaly in Indian stock market.